IOS-Based Mobile Service Ordering Application Using Wireframe and Figma - Yoyon Efendi; Ilham Perdana; Muhammad Raihan; Rometdo Muzawi; Nurul Utami; Tashid (JAIA - Journal of Artificial Intelligence and Applications, 2022)
Technological developments are increasingly growing rapidly so that everyone cannot avoid these technological advances. The technology in question covers all aspects of life, therefore here we create an application that is expected to help the community in finding tenants for IOS-based services, with the aim of helping people who are difficult in terms of finding service providers who want to be hired to help with their daily homework day.